MODERN INNOVATIVE TECHNOLOGIES OF CORRECTIVE WORK IN THE PROFESSIONAL ACTIVITIES OF THE SPEECH THERAPIST TEACHER (Psychology Travelogs, 2024)
The article examines the use of innovative technologies in the professional activity of a speech therapist teacher, the purpose of which is to improve corrective and developmental work with children.It has been proven that, alongside the traditional ones, these technologies are, in particular, information and communication technologies as communication methods of interaction with information, distance educational technologies used in organizing work online, pedagogical technologies using non-traditional techniques for speech therapy: aromatherapy, chromotherapy, bibliotherapy, etc., while the use of aromatherapy, namely essential oils of flowers, fruits and wood, forest scents, as well as candles with various soothing scents promote relaxation and calm down during rest, health-preserving technologies (cryotherapy, breathing exercises, etc.), art therapy (treatment with creativity ), fairy-tale therapy (correction through the staging of fairy tales, playing), esthetotherapy (influence through visual arts), music therapy (influence through the perception of music), sand therapy, cone therapy and acorn therapy (tactile effect of sand on sensory receptors), kinesiotherapy (speech and phonetic rhythms ) and others, contribute to achieving the maximum possible success in overcoming speech disorders in preschool children.The value of innovative therapeutic technologies is determined, which consists in correcting and overcoming psychological and speech disorders in preschool children.It has been concluded that isotherapy and fairy-tale therapy should be used in the correction of speech disorders. In particular, the main tasks of isotherapy are the development of fine motor skills, mastering the skills of spatial orientation on paper, the activation of an active vocabulary due to the introduction of new concepts and terms in the course of artistic activity, the development of imagination, the ability to express one's thoughts and feelings, including verbally.It was found that the use of innovative technologies will help to diversify the education of preschool children with delayed development of mental processes and unformed sensory reactions when forming pronunciation.
Keywords: speech therapist teacher; innovative technologies; art therapy; isotherapy; fairy tale therapy; music therapy